Venture Capital, Credit, and FinTech Start-Up Formation: A Cross-Country Study. (September 2022) - Kolokas, Dimitrios; Vanacker, Tom; Veredas, David; Zahra, Shaker A.
Growing FinTech entrepreneurship is a recent global phenomenon. Drawing on the national innovation systems framework, we examine how countries' venture capital (VC) and credit markets differently affect FinTech entrepreneurship across countries. We argue that with their established and globally diffused norms and practices, VC investors—but not banks—require a critical mass of FinTech entrepreneurship in a country to more positively influence FinTech entrepreneurship. Moreover, we argue that VC and credit markets are substitutes, especially in countries with more FinTech entrepreneurship. Using quantile regressions on data from 53 countries, we find support for our hypotheses.